Unpredictable environments lead to the evolution of parental neglect in birds - Shana M. Caro; Ashleigh S. Griffin; Camilla A. Hinde; Stuart A. West (Nature Communications, 2016)
The response of parents to offspring begging behaviour is hugely variable in birds, but what mediates this response is not known. In a meta-analysis across 143 species, Caro et al. show that variation in offspring begging and parental care is a function of environmental quality and predictability.